2019
DOI: 10.1111/acel.12929
|View full text |Cite
|
Sign up to set email alerts
|

Tau overexpression impairs neuronal endocytosis by decreasing the GTPase dynamin 1 through the miR‐132/MeCP2 pathway

Abstract: Tauopathies are a class of neurodegenerative diseases that are characterized by pathological aggregation of tau protein, which is accompanied by synaptic disorders. However, the role of tau in endocytosis, a fundamental process in synaptic transmission, remains elusive. Here, we report that forced expression of human tau (hTau) in mouse cortical neurons impairs endocytosis by decreasing the level of the GTPase dynamin 1 via disruption of the miR‐132‐MeCP2 pathway; this process can also be detected in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…The deregulation of miRNAs has been well validated in AD ( Liu et al, 2017 ; Wang et al, 2018 ; Tang et al, 2019 ; Xie et al, 2019 ; Hou et al, 2020 ). In the present study, we found that miR-144-3p was upregulated in the hippocampi and mPFC of mice with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation of miRNAs has been well validated in AD ( Liu et al, 2017 ; Wang et al, 2018 ; Tang et al, 2019 ; Xie et al, 2019 ; Hou et al, 2020 ). In the present study, we found that miR-144-3p was upregulated in the hippocampi and mPFC of mice with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miR-132 plays an important role in the pathogenesis of AD by regulating apoptosis and GTDC-1/CDK-5/tau phosphorylation signaling mechanisms ( Liu and Zhang, 2019 ). Notably, in human tau-overexpressing neurons, methyl-CpG-binding protein 2 (MeCP2) levels were increased, while miR-132 was decreased, and miR-132 was found to negatively regulate MeCP2 expression both in vitro and in vivo ( Xie et al, 2019 ). Xie et al, found that miR-132 deficiency led to increased tau expression, phosphorylation, and aggregation in mice.…”
Section: Neuropathogenesis Of Mir-132 In Admentioning
confidence: 99%
“…Xie et al, found that miR-132 deficiency led to increased tau expression, phosphorylation, and aggregation in mice. In addition, miR-132 regulated tau expression and phosphorylation, and thus contributed to tauopathy in AD by regulating MeCP2 levels, suggesting a vicious cycle of tau-miR-132-MeCP2-tau abnormalities in AD ( Xie et al, 2019 ). Smith et al, found that miR-132 deficiency led to increased tau expression, phosphorylation and aggregation in mice, as well as demonstrating that miR-132 directly targeted tau mRNA to regulate its expression, by using reporter assays and cell-based studies.…”
Section: Neuropathogenesis Of Mir-132 In Admentioning
confidence: 99%
“…An increasing number of miRNAs have emerged as biomarkers for the diagnosis and prognosis of various neurological diseases (Wang et al, ; Xie et al, ). Accumulating data imply that differential miRNA expression profiles detected by sequencing are involved in developing cognitive defects (Tang et al, ) and Parkinson's disease (Su et al, ).…”
Section: Discussionmentioning
confidence: 99%